The Effect of Special and Training- Competition Exercises on the Development of the Throws Standing Techniques for Junior Judokas - Tariq, Uoday; Bassim, Hasaneen (Journal of Physical Education, 2015)
The Judo sport developed widely specially in last years because of using sport science in proper methods, emerged the importance of research in the use of exercise private and semi-competition to develop some throwing skills to stand (Tachi-waza), which is one of the more wrestling skills Judo used to weigh (60-66) kg especially in their own competitions in this play, is the research problem in the lack of the use of coaches to exercise private and semi-competition running on the performance skills of skills under development, causing a state of lack of direct targeting of exercises designed for those skills properly and according to skill performance requirements, so has the goal of research is to preparation of private and semi-competition exercises to develop some of the skills of throwing stand (Tachi-waza) for young judo wrestlers. The researcher used two system (pilot, officer) dependent appropriate experimental method in such kind of research. The researcher choose the sample of young judo wrestlers ages (18-21 years) of some clubs Baghdad province of b (20) Club then chose researcher intentional way of them (16) judo wrestler representing clubs (police, youth and future) by (8) Judo wrestlers from all four of the weight of each club (60-66) kg the most important conclusions were that there were significant differences in all skill tests, and has been recommending the use of private and semi-competitive exercise in the development of the skills used in the search